Pitch Lake, La Brea, Trinidad. - (:unkn) unknown (Davidson and Todd Ltd., Trinidad, 2010)
The men in this vintage postcard appear to be on an excursion to the pitch lake and the pitch lake looks more like a river fringed with trees and grasses than the usual bare pitch lake. After heavy rainfall water settles on the lake causing ponds such as those seen here.
Colour: Sepia; Style: Landscape; Other: Unbordered; Divided
Keywords: Trinidad and Tobago; Postcards; Men--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--La Brea; Clothing and dress--Trinidad and Tobago; Asphalt industry--Trinidad and Tobago; Pitch; Hats--Trinidad and Tobago; [1912]; Pitch Lake, The (La Brea)